Screening of potato germplasm for resistance to stem necrosis - S.K. PANDEY2 and K.K. SRIVASTAVA1, R.B. SINGH1, S.M. PAUL KHURANA2 (Indian Phytopathology, 2002)
During the autumn of 1995-96 and 1996-97 at Agricultural Research Station, Ummedganj, Kota, Rajasthan, India, a total of 62 varieties/advanced hybrids and TPS populations of potatoes were screened for resistance to stem necrosis, a disease caused bya tospovirus [?potato stem necrosis tospovirus], under field conditions with early plantings. Their DI (disease incidence) and DX (disease index) varied from 1-70% and 0.1-3.5, respectively. Varieties Kufri Bahar (Avg. DI=59%; DX=2.95) followed by Kufri Chandramukhi (Av. DI=46%; DX=2.3) were highly susceptible while Kufri Sindhuri showed the greatest (Avg. DI=3%; DX=0.15) resistance. Among the hybrids tested, PS/F-220, JN-189 and MS/82-717 showed low DI (